Modernizing Currency Exchange Rate Data Integration with Data Lake Technology: A Master Data Management Approach - Elfvengren, Patrik (2025)
This thesis explores the application of Data Lake technology in enhancing the integration and management of currency exchange rate data within a global enterprise. The study addresses two critical challenges in the existing solution: inefficient incident management and unclear governance structures. By leveraging a Design Science Research Methodology (DSRM), the research develops and evaluates a design for a new Data Lake Currency Rates Solution that utilizes a Data Lake architecture to centralize and streamline the flow of currency rate data. The proposed solution replaces outdated systems and complex integrations with a modern, scalable, and flexible architecture that improves data traceability, validation, and accessibility. Master Data Management (MDM) principles and ITIL-based incident management practices are integrated into the design to ensure data quality, accountability, and operational resilience. Qualitative interviews with key stakeholders validate the effectiveness of the new solution, highlighting improvements in technical clarity, role definition, and support responsiveness. However, the study also identifies the need for clearly defined data ownership and end-to-end solution accountability to fully realize the benefits of the new model. The findings demonstrate that when Data Lake technology is aligned with thought out governance and MDM frame-works it can significantly enhance enterprise data integration processes. This research contributes practical insights for organizations seeking to modernize their data infrastructure and offers a replicable model for managing business-critical financial or market data in complex IT environments.